Strategi Guru Dalam Internalisasi Nilai Karakter Religius Untuk Membentuk Generasi Emas di Masa Depan (Studi Kasus di SD Unggulan Edi Mancoro, Tuntang) - Umam, Muhamad Khoerul; Pratama, M. Rafirsa Agung; Faisyawi, Walid (Jurnal DinamikA, 2025)
The development of the digital world today seems to have started to worry, it takes the role of parents and educational institutions to supervise their children as well as familiarize good behaviors, one of which is to use a religious approach. Educational institutions that focus on religious values are usually accommodated by religious-based educational institutions, such as Madrasah Ibtidaiyah. However, SD Unggulan Edi Mancoro, which is a private education and is not accommodated by religious educational institutions, has a different focus. SD Unggulan Edi Mancoro chooses to focus on building the religious character of its students. This article seeks to analyze the learning process at SD Unggulan Edi Mancoro in internalizing its religious character values. This research is a type of field research using a descriptive qualitative approach. The data obtained in this study are through interviews, teaching journals, and notes related to the internalization of religious values in each lesson. The data were then collected and analyzed using the theory of character building according to Maragustam. The teacher's strategy at Edi Mancoro Primary School in internalizing religious character values is through habituation, moral knowing, feeling and loving good, moral acting, moral modeling, and repentance which are carried out in the learning process every day